Strain and electric field tuning of semi-metallic character WCrCO2MXenes with dual narrow band gap - Bafekry, A; Akgenc, B; Ghergherehchi, M; Peeters, F M (Journal of physics. Condensed matter, 2020)
Motivated by the recent successful synthesis of double-M carbides, we investigate structural and electronic properties of WCrC and WCrCO2monolayers and the effects of biaxial and out-of-plane strain and electric field using density functional theory. WCrC and WCrCO2monolayers are found to be dynamically stable. WCrC is metallic and WCrCO2display semi-metallic character with narrow band gap, which can be controlled by strain engineering and electric field. WCrCO2monolayer exhibits a dual band gap which is preserved in the presence of an electric field. The band gap of WCrCO2monolayer increases under uniaxial strain while it becomes metallic under tensile strain, resulting in an exotic 2D double semi-metallic behavior. Our results demonstrate that WCrCO2is a new platform for the study of novel physical properties in two-dimensional Dirac materials and which may provide new opportunities to realize high-speed low-dissipation devices.Motivated by the recent successful synthesis of double-M carbides, we investigate structural and electronic properties of WCrC and WCrCO2monolayers and the effects of biaxial and out-of-plane strain and electric field using density functional theory. WCrC and WCrCO2monolayers are found to be dynamically stable. WCrC is metallic and WCrCO2display semi-metallic character with narrow band gap, which can be controlled by strain engineering and electric field. WCrCO2monolayer exhibits a dual band gap which is preserved in the presence of an electric field. The band gap of WCrCO2monolayer increases under uniaxial strain while it becomes metallic under tensile strain, resulting in an exotic 2D double semi-metallic behavior. Our results demonstrate that WCrCO2is a new platform for the study of novel physical properties in two-dimensional Dirac materials and which may provide new opportunities to realize high-speed low-dissipation devices.